2004
DOI: 10.1080/14647270410001720464
|View full text |Cite
|
Sign up to set email alerts
|

The presence of abnormal spermatozoa in the ejaculate: Did apoptosis fail?

Abstract: With the successful use of Assisted Reproduction, in particular intracytoplasmic sperm injection (ICSI), to treat infertile couples we have become less discriminating with the quality of spermatozoa we use to treat our patients. Numerous studies have shown the presence of nuclear DNA strand breaks in human ejaculated spermatozoa. The reason why human spermatozoa, in particular from men with abnormal semen parameters, possess these abnormalities in their nuclear DNA is still not clear. Two processes that have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 42 publications
(35 reference statements)
1
51
0
5
Order By: Relevance
“…One of the hypothesized triggers of testis apoptosis is the impairment of sperm chromatin maturation (60). This idea is supported by the association between apoptotic markers and cell immaturity (24,46).…”
Section: E C H a N I S M S O F S P E R M D N A F R A G M E N T A T supporting
confidence: 51%
“…One of the hypothesized triggers of testis apoptosis is the impairment of sperm chromatin maturation (60). This idea is supported by the association between apoptotic markers and cell immaturity (24,46).…”
Section: E C H a N I S M S O F S P E R M D N A F R A G M E N T A T supporting
confidence: 51%
“…Numerous studies have now shown the presence of nuclear DNA strand breaks and apoptosis in human ejaculated spermatozoa from infertile patients and the abnormal persistence of apoptotic marker proteins (32). Why human spermatozoa possess these abnormalities is still not clear (33).…”
Section: Discussionmentioning
confidence: 99%
“…Several theories have been put forward to explain the existence of these abnormal cells, [5][6][7] present also in otherwise normal ejaculates as assessed by the World Health Organisation's (WHO) guidelines for conventional semen analysis (WHO, 1999). It has been proposed that sperm DNA damage can originate from oxidative stress, from unligated strand breaks physiologically formed during spermatogenesis to help the process of chromatin remodelling, and from defective or 'abortive' apoptotic processes [8][9][10] initiated post meiotically when cells are no longer able to complete the classical pathways of programmed cell death. 1, 3,11 Notably, it has been stressed that these mechanisms are not mutually exclusive and, in reality, DNA damage may arise from combinations of all three mechanisms.…”
Section: Introductionmentioning
confidence: 99%